Alternating Current Electroluminescent Device Powered by Triboelectric Nanogenerator with Capacitively Driven Circuit Strategy. (6th November 2021) - Liu, Xu; Zhang, Maoyuan; Yang, Ze; Wang, Hao; Chen, Jiaqi; Wang, Zhaozheng; Lu, Yijia; Chen, Yibao; Ji, Linhong; Cheng, Jia
Abstract: Alternating current electroluminescent (ACEL) devices have the advantages of low power consumption, easy preparation, and good flexibility. However, a high‐voltage alternating current is usually demanded for driving devices, resulting in a strong dependence on an energy system with little wearing‐comfort and portability. Herein, a novel and feasible technology for lighting up ACEL via triboelectric nanogenerator (TENG) is proposed. The most significant innovation is the use of a capacitively driven circuit to significantly increase the output voltage of the generator, so as to get rid of the constraints of area, materials, environmental humidity, etc. Compared with direct connection of electroluminescent devices with TENG, the peak‐to‐peak voltage is 2.3 times that of the traditional method, and the transferred charges are increased to 3.4 times. This work realizes the self‐powered electroluminescent devices based on triboelectric nanogenerator with a compact composite structure, which not only is more effective but also has better flexibility and portability in the applications of soft robots, functional displays, smart skins, and wearable electronics. Besides, this capacitively driven circuit strategy is universal for those capacitive loads with demand for high voltage AC, which proposes a simple and practical approach to magnify the amplitudes of AC voltage and current from triboelectric nanogenerators. Abstract : A novel and feasible technology for lighting up ACEL via a triboelectric nanogenerator (TENG) is proposed. The most significant innovation is the use of a capacitively driven circuit to greatly increase the output voltage of generator. Compared with direct connection of electroluminescent devices with TENG, both the peak‐to‐peak voltage and the transferred charges are apparently improved.